2004
DOI: 10.1001/jama.292.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tenofovir DF vs Stavudine in Combination Therapy in Antiretroviral-Naive Patients<SUBTITLE>A 3-Year Randomized Trial</SUBTITLE>

Abstract: 753 patients infected with HIV who were antiretroviral naive were screened and 602 patients entered the study. Intervention Patients were randomized to receive either tenofovir DF (n=299) or stavudine (n=303), with placebo, in combination with lamivudine and efavirenz. Main Outcome Measure Proportion of patients with HIV RNA levels of less than 400 copies/mL at week 48. Results In the primary intent-to-treat analysis in which patients with missing data or who added or switched antiretroviral medications before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
897
12
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,261 publications
(989 citation statements)
references
References 28 publications
61
897
12
12
Order By: Relevance
“…25 The association of weight loss, body fat changes and stavudine use was also observed in a large randomized trial, comparing stavudine with tenofovir-based ART. 18 This study reported that, after an initial increase, the average body weight of the study population returned to baseline levels by three years of stavudine intake, paralleled by a gradual peripheral fat loss. Although the difference did not reach statistical significance, patients with poor treatment adherence appeared to have less weight loss after the first year of ART in our study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…25 The association of weight loss, body fat changes and stavudine use was also observed in a large randomized trial, comparing stavudine with tenofovir-based ART. 18 This study reported that, after an initial increase, the average body weight of the study population returned to baseline levels by three years of stavudine intake, paralleled by a gradual peripheral fat loss. Although the difference did not reach statistical significance, patients with poor treatment adherence appeared to have less weight loss after the first year of ART in our study.…”
Section: Discussionmentioning
confidence: 84%
“…[14][15][16] Although never specifically addressed, several studies suggest a potential association of lipoatrophy with weight loss. 15,17,18 We conducted a study on patients on stavudinecontaining ART to (a) determine the proportion who manifest weight loss after one year of ART, (b) examine the association between such weight loss and a number of variables namely: lipoatrophy, virological failure, adherence and on-treatment CD4 count and (c) assess the validity and predictive values of weight loss to identify patients with lipoatrophy.…”
Section: Introductionmentioning
confidence: 99%
“…concluded that the probability of osteopenia and osteoporosis would be over 6-fold and almost 4-fold higher in HIV-infected than in uninfected populations respectively (23). In line with these data, in a clinical trial that evaluated BMD before starting ART, the prevalence of osteopenia at the start of ART was in a range of 23 to 28%, clearly higher than that in the general population (24).…”
Section: Hiv and Low Bone Massmentioning
confidence: 76%
“…The authors reported a relative risk of 2.5 for osteopenia in patients with ART compared with untreated patients. In fact, other longitudinal studies and clinical trials conducted to date also suggest that ART is associated with low bone mass (24,27).…”
Section: Art and Low Bmdmentioning
confidence: 99%
“…They cause increases in total cholesterol, triglycerides and LDL. Among that category of drugs Stavudine is the drug associated with severe dyslipidemia [8]. The presence of an atherogenic lipid profile in HIV patients on antiretroviral therapy makes these patients more susceptible to cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%